David Wills and the Tropological Machinery of Life. - Kuiken, Kir (Derrida Today, 2025)
This essay argues that David Wills's work re-articulates the relation between technology and language by treating language as a form of mechanicity engendered by tropological substitution. This tropological machinery, Wills suggests, operates automatically while producing and subtending supposedly 'natural' phenomena. The essay traces this argument through Wills's early work up to his book Inanimation, arguing that these tropological dimensions of language become an increasingly important part of his account of how technology operates reflexively. The essay closes with an argument for how tropological language is a central figure for what Wills calls 'inanimation', the constantly displaced border between life and its others—death and the inanimate. It concludes that Wills's conception of the relation between language and technology produces a unique 'zone of indistinction' between the animate and the inanimate, a form of 'life' that is no longer purely biological.